2010
DOI: 10.1158/0008-5472.can-10-0917
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Pyridocarbazole and Benzopyridoindole Derivatives that Inhibit Protein Kinase CK2

Abstract: The alkyloid compound ellipticine derived from the berrywood tree is a topoisomerase II poison that is used in ovarian and breast cancer treatment. In this study, we report the identification of ellipticine derivatives and their tetracyclic angular benzopyridoindole analogues as novel ATP-competitive inhibitors of the protein kinase CK2. In vitro and in vivo assays showed that these compounds have a good pharmacologic profile, causing a marked inhibition of CK2 activity associated with cell cycle arrest and ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 39 publications
3
59
0
4
Order By: Relevance
“…The ellipticine derivative N2-methyl-9-hydroxyellipticium has been used in the treatment of breast cancer, but it has been retrieved because of its toxicity. Previous studies have shown that Pyr1 is a weak DNA intercalator and has no effect on topoisomerase II (26).…”
Section: Pyr1 Is Well Tolerated In Mice and Shows Anticancer Activitymentioning
confidence: 94%
“…The ellipticine derivative N2-methyl-9-hydroxyellipticium has been used in the treatment of breast cancer, but it has been retrieved because of its toxicity. Previous studies have shown that Pyr1 is a weak DNA intercalator and has no effect on topoisomerase II (26).…”
Section: Pyr1 Is Well Tolerated In Mice and Shows Anticancer Activitymentioning
confidence: 94%
“…The binding mode of compound 31 predicted by molecular docking is similar to the interactions of compounds 18E and 19E with CK2, three-dimensional structures of these complexes were determined by X-ray crystallography 16 . All three compounds form hydrogen bonds with kinase hinge-region by the oxygen atom, employing carboxylic acid oxygen in the case of compound 31 and oxygen of the phenoxy group in the case of compounds 18E and 19E.…”
Section: Resultsmentioning
confidence: 89%
“…La mise au point d'un test enzymatique simple et robuste a permis d'identifier des inhibiteurs présentant des propriétés anticancéreuses prometteuses (Tableau I). Ainsi, des dérivés des pyridocarbazoles et des benzopyridoindoles ont été caractérisés comme des inhibiteurs de CK2, agissant comme compétiteurs de l'ATP et présentant des propriétés antiprolifératives dans un modèle de xénogreffe de glioblastome humain [5]. Trois dérivés de REVUES [22].…”
Section: Start-up Et/ou Transfert Vers Un Partenaire Industrielunclassified
“…Utilisés quotidiennement en laboratoire, les tests et le savoir-faire des chercheurs constituent une ressource largement sous exploitée pour le criblage et la découverte de molécules bioactives. Le champ d'application de ces molécules ne se limite pas au secteur du médicament : les molécules chimiques découvertes au centre de criblage pour des molécules bioactives du CEA-Grenoble (CMBA-Grenoble) se révèlent des outils prometteurs tant en recherche fondamentale [3][4][5][6][7][8][9] que pour des applications dans les domaines de la santé 2 , de l'environnement ou des bioénergies 3 .…”
unclassified